Localization of Enterobacterial Common Antigen: Immunogenic and Nonimmunogenic Enterobacterial Common Antigen-Containing Escherichia coli - Rinno, J. (1980)
In rabbits immunized with intact bacteria, the immune response to the enterobacterial common antigen (ECA) predominantly consists of the production of immunoglobulin M antibodies. This is not dependent on whether the animals are immunized for a short (2 weeks) or a long (3 months) period of time. The highest ECA-specific immunoglobulin G titers were observed after a short immunization with living bacteria. ECA-specific antisera were obtained by absorption with appropriate ECA-negative mutants. The absorbed antisera were then separated on Sephadex G-200. The resulting immunoglobulin G fractions were conjugated to ferritin by glutardialdehyde and used to visualize the distribution of ECA in E. coli. Bacterial strains either possessing the immunogenic form of ECA (F470, 2387) or solely the nonimmunogenic form (F614) or being devoid of both (ECA-negative mutants F1283 and F1327) were labeled with the conjugates. Freezeetchings of ferritin-labeled strains showed a dense labeling of the outer membrane in case of ECA-immunogenic strains, an essentially weaker labeling of the non-immunogenic ECA mutant and, as expected, no labeling of ECA-negative mutants. Comparable results were obtained with the indirect immunofluorescence technique: the whole cell envelope of strain F470 showed a brilliant fluorescence, whereas a much lesser, spotty distribution of fluorescence was noted with strain F614 and none at all was noted with the ECA-negative strains. These data show that ECA is localized in the outer membrane of ECA-containing strains and further demonstrate that there is more in the immunogenic strains than in the nonimmunogenic ones.